Debating the global financial architecture - Armijo, Leslie Elliott (SUNY series in global politics., 2002)
Political scientists and economists set out their disparate views on what global financial structure would best promote world economic growth and therefore political stability. Most are American academics, but some are policy makers and advisors, and some are from other countries. Most of the 10 studies were last revised in 2000. Annotation copyrighted by Book News, Inc., Portland, OR.